Negative electrode material, negative electrode plate, electrochemical device and preparation method of negative electrode material

Through the graphite material mixed with primary and secondary particles, combined with the amorphous carbon cladding layer, the problem of low peeling force of the negative electrode sheet of lithium-ion battery is solved, the battery performance and stability are improved, and the preparation process is simplified.

CN119153636APending Publication Date: 2024-12-17ENVISION DYNAMICS TECH (JIANGSU) CO LTD +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310720495.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-16
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

After granulation, the negative electrode material of commercial lithium-ion batteries has low tap density and large specific surface area, which leads to the problem of low peeling force of the negative electrode sheet.

Method used

The graphite material mixed with primary particles and secondary particles is used to form a composite graphite precursor by mixing the graphite substrate and the coating agent at the softening temperature of the graphite substrate and the coating agent, and the negative electrode material is obtained through high-temperature graphitization treatment. The coating layer includes none. Carbon is shaped to increase tap density and specific surface area.

Benefits of technology

The electrode stripping force of the negative electrode sheet and the DC resistance of the battery are improved, the structural stability and electrochemical performance of the negative electrode material are enhanced, the preparation process is simplified, and the cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153636A_ABST
    Figure CN119153636A_ABST
Patent Text Reader

Abstract

The invention provides a negative electrode material, a negative electrode plate, an electrochemical device and a preparation method of the negative electrode material, and belongs to the technical field of secondary batteries, the negative electrode material comprises primary particles and secondary particles; wherein the primary particles and the secondary particles are graphite materials, the surfaces of the primary particles and the secondary particles are coated with coating layers, and the coating layers comprise amorphous carbon; moreover, the tap density of the negative electrode material is 1.0-1.3 g / cm < 3 >, and the specific surface area of the negative electrode material is 1.0-1.3 m < 2 > / g. The negative electrode material disclosed by the invention has proper tap density and specific surface area, and the prepared negative electrode pole piece has higher pole piece stripping force, so that the direct-current resistance of an assembled battery and the yield of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a negative electrode material, a negative electrode plate, an electrochemical device and a method for preparing the negative electrode material. Background Art

[0002] In today's era, lithium-ion secondary batteries are widely used in digital, power and energy storage fields due to their high energy density, long cycle life, fast charging capability, low cost, and environmental protection. With the gradual increase in market share, the market has put forward higher requirements for lithium-ion batteries, such as higher energy density, longer cycle performance, and shorter fast charging time.

[0003] At present, the negative electrode materials of commercial lithium-ion batteries are mainly graphite materials. Graphite materials have high gram capacity and low voltage platform, and their charging capacity on the negative electrode plate can be improved through granulation. However, the tap density of the secondary granular graphite after granulation is low and the specific surface area is large, and the prepared negative electrode plate is prone to low peeling force processing problems.

[0004] Therefore, it is necessary to design a negative electrode material, a negative electrode plate, an electrochemical device and a method for preparing the negative electrode material, and provide a graphite material mixed with primary particles and secondary particles, so as to solve the above problems. Summary of the invention

[0005] In view of the above shortcomings of the prior art, the present invention provides a negative electrode material, a negative electrode plate, an electrochemical device and a method for preparing the negative electrode material, so as to solve the technical problems that the graphite material has a low tap density after granulation, a large specific surface area, and the prepared negative electrode plate is prone to low peeling force.

[0006] To achieve the above-mentioned object and other related objects, the present invention provides a negative electrode material, the negative electrode material comprising: primary particles and secondary particles;

[0007] The primary particles and the secondary particles are graphite materials, the surfaces of the primary particles and the secondary particles are coated with a coating layer, and the coating layer includes amorphous carbon; and the tap density of the negative electrode material is 1.0 to 1.3 g / cm 3 The specific surface area of ​​the negative electrode material is 1.0 to 1.3 m 2 / g.

[0008] In an example of the present invention, the coating layer has a thickness of 0.01-0.1 μm.

[0009] In one example of the present invention, the density ρ3 of the coating layer is 1.4-1.55 g / cm 3 , the density ρ3 is Wherein, ρ2 and ρ1 are true densities obtained by testing the negative electrode material before and after coating, and H2 and H1 are heat absorption amounts obtained by testing the negative electrode material before and after coating.

[0010] In an example of the present invention, the amorphous carbon includes hard carbon.

[0011] On the other hand, the present invention provides a method for preparing the negative electrode material described in any of the above examples, and the preparation method comprises the following steps: mixing and granulating a graphite substrate and a coating agent to obtain a secondary particle graphite precursor; breaking up and deagglomerating the secondary particle graphite precursor so that a primary particle graphite precursor is dissociated from the secondary particle graphite precursor to obtain a composite graphite precursor; and graphitizing the composite graphite precursor to obtain a negative electrode material.

[0012] In one example of the present invention, the mass ratio of the graphite substrate to the coating agent is 100:(2-15).

[0013] In one example of the present invention, the graphite substrate includes at least one of petroleum-based non-needle coke, petroleum-based needle coke, coal-based non-needle coke and coal-based needle coke.

[0014] In an example of the present invention, the coating agent includes at least one of phenolic resin, polyester resin and polyamide resin.

[0015] In one example of the present invention, the softening temperature of the coating agent is 80°C to 150°C.

[0016] The present invention also provides a negative electrode plate, which includes a negative electrode current collector and a negative electrode active material layer arranged on the negative electrode current collector, and the negative electrode active material layer includes the negative electrode material described in any one of the above examples.

[0017] The present invention also provides an electrochemical device, which includes a positive electrode plate, a separator, an electrolyte, and a negative electrode plate as described in any one of the above examples.

[0018] The negative electrode material of the present invention provides a composite graphite material mixed with primary particles and secondary particles, and the negative electrode material has a suitable tap density and specific surface area (tap density is 1.0-1.3 g / cm 3 , with a specific surface area of ​​1.0 to 1.3 m 2 / g), the prepared negative electrode sheet has a higher sheet peeling force, which is beneficial to improve the DC resistance of the assembled battery and the battery yield. Therefore, the present invention effectively overcomes some practical problems in the prior art and has high utilization value and use significance. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 Schematic diagram of a process for preparing a negative electrode material in one embodiment of the present invention. DETAILED DESCRIPTION

[0021] The following is an explanation of the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the features in the following embodiments and the embodiments can be combined with each other without conflict. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods for which specific conditions are not specified in the following examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers.

[0022] It should be noted that the terms such as "upper", "lower", "left", "right", "middle" and "one" etc. used in this specification are only for the convenience of description and are not intended to limit the scope of implementation of the present invention. Changes or adjustments to their relative relationships, without substantially changing the technical content, should also be regarded as the scope of implementation of the present invention.

[0023] The present invention provides a negative electrode material, which is used to make a negative electrode plate of an electrochemical device. An electrochemical device generally includes a positive electrode material, a negative electrode material, an electrolyte, a diaphragm, and corresponding connecting accessories and circuits. The positive and negative electrode materials can deintercalate lithium ions to achieve energy storage and release, the electrolyte is a carrier for lithium ions to be transmitted between the positive and negative electrodes, and the diaphragm can pass lithium ions but is not conductive, thereby separating the positive and negative electrodes to prevent short circuits. The positive and negative electrode materials generally play a decisive role in key performance factors such as the energy storage function of a lithium battery, the energy density of its battery cell, cycle performance, and safety.

[0024] The negative electrode material provided by the present invention includes primary particles and secondary particles, that is, the negative electrode material is a composite material mixed with primary particles and secondary particles, and the mixing ratio of the primary particles and the secondary particles in the negative electrode material is not limited, and can be adjusted according to the required tap density and specific surface area in practical applications. Among them, the primary particles and the secondary particles are both graphite materials, the negative electrode material uses the primary particles and the secondary particles as the core body, and the surface of the primary particle core body and the secondary particle core body is coated with a coating layer, and the coating layer includes amorphous carbon.

[0025] Since the negative electrode material is a composite graphite material mixed with primary particles and secondary particles, the negative electrode material has a more suitable tap density and specific surface area than pure secondary particle graphite (that is, it has a higher tap density and a lower specific surface area than secondary particle graphite), which can make the negative electrode material have higher active ion and electron rapid transmission ability and better structural stability, and when used as the negative electrode active material layer to prepare the negative electrode sheet, the negative electrode sheet will also have a higher sheet peeling force.

[0026] Specifically, the tap density of the negative electrode material is 1.0 to 1.3 g / cm 3 , for example 1.0g / cm 3 , 1.05g / cm 3 , 1.07g / cm 3 , 1.08g / cm 3 , 1.09g / cm 3 , 1.10g / cm 3 , 1.15g / cm 3 , 1.17g / cm 3 , 1.20g / cm 3 , 1.25g / cm 3 or 1.30g / cm 3 ; Correspondingly, the specific surface area of ​​the negative electrode material is 1.0 to 1.3 m 2 / g, for example 1.0m 2 / g, 1.02m 2 / g, 1.04m 2 / g, 1.06m 2 / g, 1.08m 2 / g, 1.10m 2 / g, 1.12m 2 / g, 1.15m 2 / g, 1.17m 2 / g, 1.20m 2 / g, 1.25m 2 / g or 1.30m 2 / g.

[0027] In a preferred example, the tap density of the negative electrode material is 1.05 to 1.15 g / cm 3 The specific surface area of ​​the negative electrode material is 1.01 to 1.26 m 2 / g. In this example, the tap density and specific surface area parameters of the negative electrode material are between those of pure primary graphite particles and secondary graphite particles. The mixture of primary and secondary particles enables the particles of the negative electrode material to have a larger contact area after being tapped, which is beneficial to the uniform distribution of the negative electrode material particles in the negative electrode film layer and the construction of ion channels, thereby improving the reversible capacity and electrical conductivity of the negative electrode material in the negative electrode sheet, while improving the chemical stability (fewer internal side reactions) and physical stability (larger electrode sheet peeling force) of the negative electrode material as a negative electrode active material layer in the negative electrode sheet.

[0028] In the present invention, the amorphous carbon coating layer may be formed by graphitization with a coating agent, and the coating agent may be an organic carbon source.

[0029] Amorphous carbon has a disordered structure and a high interlayer spacing. Therefore, the use of amorphous carbon to coat the core material can make the active ions diffuse faster in the negative electrode material particles, thereby improving the material's fast charging ability. At the same time, the amorphous carbon coating can also protect the core material, greatly reducing the graphite layer peeling caused by the co-embedding of the core material due to the solvent, so that the negative electrode material has a higher structural stability. Therefore, the negative electrode material can have a higher capacity and cycle life.

[0030] In some embodiments, the coating agent may be a resin material with different softening temperatures, such as at least one of a phenolic resin, a polyester resin, and a polyamide resin. The resin material may be coated on the surface of the graphite particles in the form of hard carbon after high-temperature graphitization, thereby improving the fast charging ability of the graphite material.

[0031] In some embodiments, the coating thickness of the negative electrode material is 0.01 to 0.1 μm, for example, 0.01 μm, 0.02 μm, 0.023 μm, 0.03 μm, 0.032 μm, 0.034 μm, 0.036 μm, 0.04 μm, 0.049 μm, 0.05 μm, 0.06 μm, 0.07 μm, 0.08 μm, 0.09 μm or 0.1 μm. Among them, the coating thickness of 0.01 to 0.1 μm in the negative electrode material is a suitable thickness, which can take into account the kinetic performance and high temperature performance of the negative electrode material; among them, if the coating thickness is less than 0.01 μm, the kinetic performance of the negative electrode material is poor, and if the coating thickness is greater than 0.1 μm, the kinetic performance of the negative electrode material after coating will not be significantly improved, but the high temperature performance will be significantly deteriorated.

[0032] In some embodiments, the coating density ρ3 of the negative electrode material is 1.4 to 1.55 g / cm3 , for example, 1.4 g / cm 3 , 1.42g / cm 3 , 1.44g / cm 3 , 1.46g / cm 3 , 1.47g / cm 3 , 1.50g / cm 3 , 1.52g / cm 3 or 1.55g / cm 3 Among them, the coating density ρ3 is calculated by the following relationship, Wherein, ρ2 and ρ1 are the true densities obtained by testing the negative electrode material before and after coating, and H2 and H1 are the heat absorption values ​​obtained by testing the negative electrode material before and after coating. The specific test method can be found in the test section below.

[0033] The inventor has found through research that there is no process method for directly preparing a mixed graphite material of primary particles and secondary particles in the prior art preparation method. The prior art preparation method requires the preparation of primary graphite particles and secondary graphite particles separately. When preparing primary graphite particles, the graphite substrate needs to be subjected to graphitization, coating and carbonization processes. When preparing secondary graphite particles, the graphite substrate needs to be subjected to granulation, graphitization, coating and carbonization processes. After the preparation of the graphite materials of primary particles and secondary particles is completed, they are mixed to obtain a graphite material mixed with primary and secondary particles. It can be seen that for the graphite material mixed with primary and secondary particles, the prior art preparation method has too many processes, and the time and process costs are too high.

[0034] To solve the above problems, the present invention provides a method for preparing a negative electrode material. The preparation method of the present invention comprises mixing and granulating a graphite substrate and a coating agent at a softening temperature before graphitization, and depolymerizing after granulation to directly obtain a graphite precursor mixed with primary particles and secondary particles. Finally, the graphite material mixed with primary particles and secondary particles can be obtained through high-temperature graphitization.

[0035] Compared with conventional preparation methods, the preparation method of the present invention combines granulation and coating into one step, and uses the fluidity of the softening coating agent to make the particles that are not firmly bonded fall off during the depolymerization process, forming a composite product of primary particles and secondary particles. The subsequent direct graphitization eliminates the step of carbonizing the graphite and the coating layer separately. The preparation method can directly prepare a graphite material mixed with primary particles and secondary particles, without the need to prepare primary particle graphite and secondary particle graphite separately, and in the subsequent step, the graphitization of the graphite substrate and the carbonization of the coating are combined into one step, thereby greatly simplifying the process steps and saving time and process costs.

[0036] Specifically, see Figure 1 , the method for preparing the negative electrode material comprises the following steps:

[0037] S1. At the softening temperature of the coating agent, the graphite substrate and the coating agent are mixed and granulated to obtain a secondary particle graphite precursor;

[0038] S2, breaking up and depolymerizing the secondary graphite particle precursor, so that the primary graphite particle precursor is dissociated from the secondary graphite particle precursor to obtain a composite graphite precursor; wherein the composite graphite precursor includes a primary graphite particle precursor and a secondary graphite particle precursor;

[0039] S3, graphitizing the composite graphite precursor to obtain a negative electrode material.

[0040] In step S1, at the softening temperature of the coating agent, the graphite substrate and the coating agent are uniformly mixed and then mechanically granulated. During the stirring process, the bonding properties of the softened coating agent can be used to aggregate the independently dispersed primary particles to form secondary particles, thereby obtaining a secondary particle graphite precursor.

[0041] In step S1, granulation can be performed using equipment known in the art, such as a granulator. The granulator generally includes a stirred reactor and a module for controlling the temperature of the reactor. By regulating the stirring speed, heating rate, granulation temperature, cooling rate, etc. during the granulation process, the granulation degree and the structural strength of the particles can be regulated to increase the gram capacity of the negative electrode material prepared by the secondary particle graphite precursor.

[0042] In step S1, the graphite substrate can be directly purchased from the market, or obtained by crushing the coke material. In some embodiments, the coke material is crushed to obtain the graphite substrate. The morphology of the graphite substrate obtained after crushing preferably includes one or more of block, spherical and quasi-spherical shapes.

[0043] In some embodiments, the graphite substrate may be selected from at least one of petroleum non-needle coke, petroleum needle coke, coal non-needle coke and coal needle coke. Preferably, the graphite substrate is petroleum needle coke.

[0044] In step S1, the coating agent may be an organic carbon source, for example, the organic carbon source may be selected from high molecular polymers, such as asphalt or resins, such as coal tar, petroleum asphalt, phenolic resin or polyamide resin.

[0045] In some embodiments, the coating agent may be a resin material with different softening temperatures, such as at least one of a phenolic resin, a polyester resin, and a polyamide resin. The resin material may be coated on the surface of graphite particles in the form of hard carbon after high-temperature graphitization, thereby improving the fast-charging ability of the graphite material, while the conventional asphalt coating agent becomes graphite after high-temperature graphitization. Preferably, the coating agent is a phenolic resin.

[0046] In some embodiments, during the granulation process of step S1, the softening temperature of the coating agent used is any temperature between 80°C and 150°C, for example, the softening temperature of the coating agent may be 80°C, 100°C, 120°C, 140°C or 150°C. Preferably, the softening temperature of the coating agent is 120°C.

[0047] In step S1, the coating agent with a suitable softening temperature range can be selected to adjust the granulation effect of the graphite substrate, so that the secondary graphite particle precursor in step S2 can be dissociated into a proper proportion of the primary graphite particle precursor, so that the tap density and specific surface area of ​​the negative electrode material finally obtained are within a suitable range (i.e., between pure primary graphite particles and secondary graphite particles), thereby taking into account the improvement of the negative electrode sheet prepared by the negative electrode material and the electrode sheet peeling force (increasing the electrode sheet peeling force) and DCR (reducing DCR). If the softening temperature of the coating agent is higher than 150°C, the fluidity of the coating agent is poor after softening, and the coating effect of the prepared negative electrode material is poor; if the softening temperature of the coating agent is lower than 80°C, the adhesiveness of the coating agent is poor after softening, and the subsequent granulation effect is poor.

[0048] In some embodiments, in step S1, the mixing mass ratio of the graphite substrate and the coating agent is 100:(2-15), for example, the mass ratio of the graphite substrate and the coating agent can be 100:2, 100:6, 100:10, 100:12 or 100:15, wherein the mass ratio is preferably 100:6.

[0049] In step S1, the graphite substrate and the coating agent are mixed in an appropriate mass ratio, which helps to improve the negative electrode sheet prepared by the negative electrode material and the electrode sheet peeling force (increasing the electrode sheet peeling force) and DCR (reducing DCR) of the lithium battery. If the amount of coating agent added is higher than the mass ratio range of the embodiment, the coating agent is added excessively, and it is easy to agglomerate during mixing. Moreover, a large coating amount will lead to low gram capacity of the prepared negative electrode material, low first efficiency, and poor high temperature performance of the prepared battery; if the amount of coating agent added is lower than the mass ratio range of the embodiment, the amount of coating agent added is too small, which is easy to lead to poor coating and granulation effects during preparation.

[0050] In step S2, due to the weak bonding of the resin coating agent and the low granulation strength, some primary particles that are not firmly bonded will fall off during the disintegration of the secondary particle graphite precursor, forming a composite graphite precursor mixed with the primary particle graphite precursor and the secondary particle graphite precursor. Compared with the negative electrode material prepared from the secondary particle graphite precursor granulated by the coating agent with strong bonding, the negative electrode material prepared by the composite graphite precursor has a higher pole piece peeling force in the negative electrode pole piece, which is conducive to improving the battery yield.

[0051] In step S2, the deagglomeration can be performed by using equipment and processes known in the art, for example, a deagglomerator can be used for mechanical deagglomeration.

[0052] In step S3, the composite graphite precursor obtained in step S2 is subjected to high-temperature graphitization treatment, so that the primary particles and secondary particles in the composite graphite precursor form a graphite core with an appropriate degree of graphitization, and the coating agent bonded to the surface of the primary particles and the secondary particles is coated on the surface of the core in the form of amorphous carbon such as hard carbon after high-temperature graphitization. In some embodiments, the temperature of high-temperature graphitization can be 2400°C to 3200°C.

[0053] In step S3, graphitization may be performed using equipment known in the art, such as a graphitization furnace, and further, an Acheson graphitization furnace.

[0054] The present invention also provides a negative electrode sheet, the negative electrode sheet comprising a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, the negative electrode active material layer comprising the negative electrode material of the present invention. The negative electrode sheet has a sheet peeling force of 10 to 20 N / m, such as 10 N / m, 11 N / m, 12 N / m, 13 N / m, 14 N / m, 15 N / m, 16 N / m, 17 N / m, 18 N / m, 19 N / m or 20 N / m.

[0055] The preparation process of the negative electrode sheet is as follows: the negative electrode material, the conductive agent acetylene black, the thickener sodium carboxymethyl cellulose (CMC), and the binder styrene butadiene rubber (SBR) are mixed at a mass ratio of 96.4:1:1.2:1.4, deionized water is added, the solid content of the slurry is adjusted to 55%, and the mixture is fully stirred to obtain the negative electrode slurry, and the negative electrode slurry is evenly coated on both sides of the negative electrode current collector copper foil, and the negative electrode sheet is prepared through drying, cold pressing, slitting and other processes. Among them, the conductive agent can also be selected from: at least one of acetylene black, carbon nanotubes, graphene, VGCF and other conductive materials; the binder can also be selected from: at least one of PVDF, PTFE and the like.

[0056] The present invention also provides an electrochemical device, the electrochemical device includes the negative electrode sheet of the present invention, the electrochemical device is such as a lithium ion battery, the battery includes a positive electrode sheet, a negative electrode sheet, a separator disposed between the positive electrode sheet and the negative electrode sheet, and an electrolyte. Among them, the positive and negative electrode materials can deintercalate lithium ions to achieve energy storage and release, the electrolyte is a carrier for lithium ions to be transmitted between the positive and negative electrodes, and the separator can pass lithium ions but is not conductive, thereby separating the positive and negative electrodes to prevent short circuits.

[0057] The positive electrode sheet, separator and electrolyte can be made of conventional materials and preparation methods in the art, as an example:

[0058] The preparation process of lithium-ion batteries is as follows:

[0059] Preparation of positive electrode sheet: The ternary positive electrode material (LiNi 0.8 Co 0.1Mn 0.1 O2), conductive carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 97:1.5:1.5, and a solvent N-methylpyrrolidone (NMP) is added, and the mixture is stirred and mixed to obtain a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is prepared through drying, cold pressing, slitting and other processes. Among them, the conductive agent can also be selected from: at least one of acetylene black, carbon nanotubes, graphene, VGCF and other conductive materials; the binder can also be selected from: at least one of PVDF, PTFE and the like.

[0060] The negative electrode sheet preparation process is as mentioned above.

[0061] Preparation of diaphragm: A PE porous membrane with a thickness of 11 μm is selected as the diaphragm. The thickness of the diaphragm is 9 μm to 18 μm; the air permeability is 180 s / 100 mL to 380 s / 100 mL; the porosity is 30% to 50%

[0062] Preparation of electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are uniformly mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then the fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0063] Assemble the battery: stack the prepared positive electrode sheet, separator, and negative electrode sheet in sequence, so that the separator is placed between the positive and negative electrode sheets to play a role of isolation. Then wrap it with aluminum plastic film, inject the above-prepared electrolyte after drying, and finally prepare a soft-pack battery (i.e., lithium-ion battery) with a capacity of 1Ah after packaging, standing, and formation.

[0064] The direct current resistance DCR of the lithium ion battery prepared from the negative electrode material of the present invention is 75-100Ω, for example, 75Ω, 76Ω, 77Ω, 80Ω, 81Ω, 83Ω, 85Ω, 87Ω, 89Ω, 90Ω, 93Ω, 95Ω, 97Ω or 100Ω.

[0065] The technical scheme of the present invention is described in detail below through several specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available products or can be prepared by conventional methods in the art.

[0066] Example 1

[0067] This embodiment provides a negative electrode material, and the preparation method of the negative electrode material is as follows:

[0068] S1. At a softening temperature of 120° C., a graphite substrate petroleum needle coke and a coating agent phenolic resin are mixed and granulated in a horizontal kettle granulation equipment in a mass ratio of 100:6 to obtain a secondary particle graphite precursor;

[0069] S2, placing the secondary particle graphite precursor into a depolymerizer to disperse and depolymerize, thereby obtaining a composite graphite precursor;

[0070] S3, placing the composite graphite precursor into a graphitization furnace, performing high-temperature graphitization treatment, and obtaining a negative electrode material.

[0071] This embodiment also uses the above negative electrode material to prepare a secondary lithium battery, and the preparation method of the secondary lithium battery is as follows:

[0072] (1) Preparation of positive electrode sheet:

[0073] The ternary positive electrode material (LiNi 0.8 Co 0.1 Mn 0.1 O2), conductive carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 97:1.5:1.5, and solvent N-methylpyrrolidone (NMP) is added, and the mixture is stirred thoroughly to obtain a positive electrode slurry; the mixture is stirred under the action of a vacuum mixer until the system is uniform and transparent to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on a 16μm aluminum foil current collector, and then the aluminum foil current collector is dried at room temperature and transferred to an oven at 80℃~120℃ for 6h, and then cold pressed and cut to obtain a positive electrode sheet.

[0074] (2) Preparation of negative electrode sheet:

[0075] The negative electrode material, conductive agent acetylene black, thickener sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) are mixed in a mass ratio of 96.4:1:1.2:1.4, and deionized water is added to adjust the solid content of the slurry to 55%, and then the mixture is fully stirred and mixed under the action of a vacuum mixer to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both sides of an 8μm negative electrode current collector copper foil; after drying at room temperature, the mixture is transferred to an oven for drying, and then cold pressed, cut, and other processes are performed to obtain a negative electrode sheet.

[0076] (3) Preparation of electrolyte:

[0077] In an argon atmosphere glove box with a water content of <10ppm, ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are uniformly mixed in a volume ratio of 1:1:1 to obtain an organic solvent. Then, the fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0078] (4) Diaphragm preparation:

[0079] A PE porous membrane with a thickness of 11 μm was selected as the separator.

[0080] (5) Assembling the battery:

[0081] The positive electrode sheet, separator and negative electrode sheet prepared above are stacked in sequence, so that the separator is placed between the positive and negative electrode sheets to play a role of isolation. Then, they are wrapped with aluminum plastic film, transferred to a vacuum oven for drying at 120°C, and sealed after injecting 3.0g / Ah of electrolyte. After standing, hot and cold pressing, formation, clamping, capacity division and other processes, a soft-pack battery (i.e., lithium-ion battery) with a capacity of 1Ah is finally prepared.

[0082] The specific steps and conditions for electrolyte formation are as follows: after the electrolyte is injected, maintain a hot pressure environment of 0.1MPa, charge at 0.02C for 17min at 45°C in a static state, stand for 5min and then charge to 0.3Ah at 0.02C, then cut off the air bag and vacuum seal, and stand at room temperature for 48h to complete the electrolyte formation.

[0083] Example 2

[0084] The difference between this embodiment and embodiment 1 is that when preparing the negative electrode material, in step S1, a coating agent phenolic resin with a softening temperature of 150° C. is selected, and the graphite-based petroleum needle coke and the coating agent phenolic resin are mixed and granulated at a softening temperature of 150° C.

[0085] Example 3

[0086] The difference between this embodiment and embodiment 1 is that when preparing the negative electrode material, in step S1, a coating agent phenolic resin with a softening temperature of 80° C. is selected, and the graphite-based petroleum needle coke and the coating agent phenolic resin are mixed and granulated at a softening temperature of 80° C.

[0087] Example 4

[0088] The difference between this embodiment and embodiment 1 is that when preparing the negative electrode material, in step S1, the graphite substrate petroleum needle coke and the coating agent phenolic resin are mixed in a mass ratio of 100:10.

[0089] Example 5

[0090] The difference between this embodiment and embodiment 1 is that when preparing the negative electrode material, in step S1, the graphite substrate petroleum needle coke and the coating agent phenolic resin are mixed in a mass ratio of 100:2.

[0091] Comparative Example 1

[0092] The difference between this comparative example and Example 1 is that when preparing the negative electrode material, in step S1, asphalt with a softening temperature of 120° C. is selected as the coating agent.

[0093] Comparative Example 2

[0094] The difference between this comparative example and Example 1 is that the preparation process of the negative electrode material includes:

[0095] The graphite substrate petroleum needle coke and asphalt (softening point is 120°C) are mixed in a mass ratio of 100:6 and put into a horizontal kettle equipment for granulation, and then subjected to high-temperature graphitization treatment in a graphitization furnace, and then mixed with a coating agent phenolic resin (softening point is 120°C) in a mass ratio of 100:6, and after carbonization treatment, secondary particle graphite is obtained;

[0096] Putting the graphite substrate petroleum needle coke into a graphitization furnace for high-temperature graphitization treatment, and then mixing it with a coating agent phenolic resin (softening point is 120°C) at a mass ratio of 100:6, and after carbonization treatment, obtaining primary particle graphite;

[0097] The primary graphite particles are mixed with the secondary graphite particles to obtain the negative electrode material.

[0098] The negative electrode materials prepared in Examples 1 to 5 and Comparative Examples 1 to 2 were subjected to tap density tests, specific surface area tests, coating layer thickness and density tests, and the negative electrode pole pieces and secondary lithium batteries prepared using the negative electrode materials in the above-mentioned embodiments and comparative examples were subjected to pole piece peeling force tests and direct current resistance (DCR) tests to verify the effects of the negative electrode materials in different embodiments on the structural stability of the negative electrode pole piece and the improvement of the discharge performance and service life of the electrochemical device.

[0099] (1) Tap density test

[0100] Tap density test instrument: Quantachrome Autotap, put 50g sample into a 100mL measuring cylinder, read the volume V1, read the volume V2 after 3000 vibrations, and calculate 50 / (V1-V2) as the tap density of the test sample.

[0101] (2) Specific surface area test

[0102] Test equipment: Quantachrome NOVA 4200e. Place the sample in the test equipment and heat to 200°C for degassing for 2 hours. Multi-point BET method: 0.05-0.3 kPa, 6 points (0.05, 0.10, 0.15, 0.20, 0.25, 0.30).

[0103] (3) DC resistance (DCR) test

[0104] At a specified temperature, when the battery is discharged to 50% SOC (state of charge, reflecting the remaining capacity of the battery) at a current of 1C, the current is increased to 4C and maintained for 30s. The difference between the updated stable voltage and the original platform voltage is detected. The ratio of its value to the 3C current value is the DC resistance of the battery. The DCR test result after the battery is fully charged for the first time is the initial DCR of the battery.

[0105] (4) Electrode peeling force test method

[0106] The negative electrode sheet was pressed with the same compression roller, cut to the same width as the glass slide, and attached to the glass slide with double-sided tape. The electrode sheet was stretched using a peeling force testing machine (equipment model: HAK-3512) from Shenzhen Kexing Precision Instrument Co., Ltd. at a stretching speed of 100 mm / min. The value after the peeling force stabilized was read as the peeling force of the electrode sheet.

[0107] (5) Test method for coating thickness and type

[0108] a. Sampling: Take samples from the 25kg bags of standard samples and their uncoated products respectively. Use a sampling spoon to take samples of 50g each from the center, upper middle, lower middle, middle left, middle right, upper left, lower left, upper right, and lower right of the sample bag. Then, fully vibrate and mix the 450g powders as test standard samples, named M1 (coated product) and M2 (uncoated product).

[0109] b. Test true density: refer to the national standard GB / T 24533-2009, take 5g of the standard test samples M1 and M2 respectively, and test them with TD-2200 true density tester. Test the true density three times respectively to obtain the average true density of samples M1 and M2 as ρ1 and ρ2;

[0110] c. Determination of coating content and type: Use "DSC differential scanning calorimeter" to detect the heat absorption value of raw material samples M1 and M2 respectively. Test three times respectively and take the average value as samples H1 and H2. The mass percentage of the coating layer is x, and the calculation formula of x is:

[0111]

[0112] x can be related to the true density ρ3 of the coating layer as follows:

[0113] ρ1=ρ2(1-x)+ρ3x

[0114]

[0115]

[0116] According to industry standards, if the true density ρ3 of the coating is less than or equal to 1.9, it is considered a hard carbon coating. If it is greater than 1.9, it is considered a soft carbon coating, which can determine the type of coating and the stability of different batches of coatings.

[0117] d. Determination of coating thickness: Referring to GB / T 24533-2009, 5g of the test standard sample M1 was taken and tested with a Mastersizer 3000 particle size tester. The volume average diameter of the sample M1 was measured three times to obtain the volume average diameter D. The coating thickness was recorded as d, and the following equation was obtained;

[0118]

[0119] According to the Cardan equation method for cubic equations, we can directly solve it. We first find that d and D differ by four orders of magnitude. Therefore, we can directly ignore the quadratic and cubic powers of d in the equation and solve it to get:

[0120]

[0121] The error between the results obtained by scanning electron microscope (TEM) and the solution by formula method is less than 1%, and the range of d obtained is less than 0.3μm, which is consistent with the actual TEM measurement.

[0122] The material parameters of the negative electrode materials in Examples 1 to 5 and Comparative Examples 1 to 2 and the test results of preparing the negative electrode plates and lithium batteries are shown in Table 1.

[0123] Table 1: Test results of negative electrode materials in negative electrode sheets and lithium batteries in Examples 1 to 5 and Comparative Examples 1 to 2

[0124]

[0125] From the material parameters and test results of the negative electrode materials in Examples 1 to 5 and Comparative Examples 1 to 2, it can be seen that the present invention provides a mixed graphite material of primary particles and secondary particles, and the tap density of the negative electrode material is 1.05 to 1.15 g / cm 3 , with a specific surface area of ​​1.0 to 1.25 m 2 / g, the coating thickness is 0.01~0.05μm, and the coating density is 1.4~1.5g / cm 3 From the test results, it can be seen that using the mixed graphite material as the negative electrode material can optimize the particle distribution of the negative electrode material in the negative electrode sheet, so that the electrode sheet peeling force of the negative electrode sheet is 10-20N / m, and the DCR of the secondary lithium battery is 75-100Ω, thereby further improving the structural stability of the negative electrode sheet and the charge and discharge capacity of the secondary lithium battery.

[0126] By comparing the data parameters and test results of the negative electrode materials in Examples 1, 2 and 3, it can be seen that the high softening temperature of the resin coating agent during preparation can reduce the tap density of the negative electrode material, increase the specific surface area of ​​the negative electrode material, reduce the pole piece peeling force of the corresponding negative electrode pole piece, and reduce the DCR of the secondary lithium battery; if the softening temperature of the resin coating agent used during preparation is low, the tap density of the negative electrode material is increased, the specific surface area of ​​the negative electrode material is reduced, the pole piece peeling force of the corresponding negative electrode pole piece is increased, and the DCR of the secondary lithium battery is increased. Therefore, the softening temperature of the coating agent selected during preparation should be controlled within a certain range (such as 80°C to 150°C in the present invention). In addition, the coating thickness and type of the negative electrode material in Examples 1 to 3 are basically the same, and the softening temperature of the coating agent has no effect on the coating thickness and type of the negative electrode material.

[0127] Comparing the data parameters and test results of the negative electrode materials in Examples 1, 4 and 5, it can be seen that when the amount of coating agent added increases, the tap density of the negative electrode material decreases, the specific surface area increases, and the coating layer thickness increases, the corresponding negative electrode pole piece stripping force decreases, and the DCR of the secondary battery decreases; when the amount of coating agent added decreases, the tap density of the negative electrode material increases, the specific surface area decreases, and the coating layer thickness decreases, the corresponding negative electrode pole piece stripping force increases, and the DCR of the secondary battery increases. Therefore, the mass ratio of the graphite substrate and the coating agent is controlled within a certain range (such as 100: (2 to 15) in the present invention), which helps to take into account the improvement of the pole piece stripping force (increasing the pole piece stripping force) and DCR (reducing the DCR) of the negative electrode pole piece and the lithium battery prepared by the negative electrode material.

[0128] By comparing the data parameters and test results of the negative electrode materials in Example 1 and Comparative Example 1, it can be seen that when the coating agent selected during preparation is changed from resin to asphalt, the prepared negative electrode material has a lower tap density, a higher specific surface area, a lower pole piece peeling force, and a coating layer thickness close to 0, but the DCR of the corresponding secondary lithium battery is significantly increased. This is because after the coating agent is changed to asphalt, the granulation degree is improved, but the asphalt coating agent becomes graphite after high-temperature graphitization, and there is no coating layer, which is not conducive to lithium ion embedding. Therefore, the DCR of the secondary lithium battery is significantly deteriorated.

[0129] For Example 1 and Comparative Example 2, it can be found that the negative electrode materials prepared in Example 1 and Comparative Example 2 are basically similar in terms of parameters such as tap density, specific surface area, coating thickness, coating density, and the corresponding negative electrode pole piece peeling force and the corresponding secondary lithium battery DCR. However, Comparative Example 1 combines granulation and coating into one step, and utilizes the fluidity of the softening coating agent to make the loosely bonded particles fall off during the depolymerization process to form a composite product of a mixture of primary particles and secondary particles. The subsequent direct graphitization eliminates the step of carbonizing the graphite and the coating layer separately. In comparison, the process of Comparative Example 2 is more cumbersome and complicated.

[0130] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A negative electrode material, characterized in that: include: Primary particles; Secondary particles; The primary particles and the secondary particles are graphite materials, and the surfaces of the primary particles and the secondary particles are coated with a coating layer, and the coating layer includes amorphous carbon; The tap density of the negative electrode material is 1.0 to 1.3 g / cm 3 The specific surface area of ​​the negative electrode material is 1.0 to 1.3 m 2 / g.

2. The negative electrode material according to claim 1, characterized in that: The coating layer has a thickness of 0.01 to 0.1 μm.

3. The negative electrode material according to claim 1, characterized in that: The density ρ3 of the coating layer is 1.4-1.55 g / cm 3 , the density ρ3 is Wherein, ρ2 and ρ1 are true densities obtained by testing the negative electrode material before and after coating, and H2 and H1 are heat absorption amounts obtained by testing the negative electrode material before and after coating.

4. The negative electrode material according to claim 1, characterized in that: The amorphous carbon includes hard carbon.

5. A method for preparing the negative electrode material according to any one of claims 1 to 4, characterized in that: include: The graphite substrate and the coating agent are mixed and granulated to obtain a secondary particle graphite precursor; The secondary graphite particle precursor is broken up and depolymerized, so that the primary graphite particle precursor is dissociated from the secondary graphite particle precursor to obtain a composite graphite precursor; The composite graphite precursor is graphitized to obtain a negative electrode material.

6. The method for preparing the negative electrode material according to claim 5, characterized in that: The mass ratio of the graphite substrate to the coating agent is 100:(2-15).

7. The method for preparing the negative electrode material according to claim 5, characterized in that: The graphite substrate includes at least one of petroleum-based non-needle coke, petroleum-based needle coke, coal-based non-needle coke and coal-based needle coke.

8. The method for preparing the negative electrode material according to claim 5, characterized in that: The coating agent includes at least one of a phenolic resin, a polyester resin and a polyamide resin.

9. The method for preparing the negative electrode material according to claim 5, characterized in that: The softening temperature of the coating agent is 80°C to 150°C.

10. A negative electrode plate, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer, and the negative electrode active material layer comprises the negative electrode material according to any one of claims 1 to 4, or the negative electrode material prepared by the preparation method according to any one of claims 5 to 9.

11. An electrochemical device, characterized in that: It comprises a positive electrode sheet, a separator, an electrolyte and the negative electrode sheet as claimed in claim 10.